PENGARUH PENDIDIKAN & PELATIHAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN BAGIAN MEKANIK PADA PT. INTRACO PENTA CABANG PEKANBARU - Silviany Hanika; Machasin '; Rendra Wasnuri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to determine the effect of education and training on employee performance partially Mechanical Section at PT. Intraco Penta Cabang Pekanbaru. To determine the effect of motivation on employee performance partially Mechanical Section at PT. Intraco Penta Cabang Pekanbaru. To determine the effect of education and training and motivation on employee performance simultaneously Mechanical Section at PT. Intraco Penta Cabang Pekanbaru. The population in this study were all employees at PT. Intraco Penta Cabang Pekanbaru, whose work on quantum mechanics. Because in this study, the authors focused only mechanic training in improving mechanical performance. The number of employees who work on quantum mechanics in 2012 as many as 80 people. For this study the policy, then the sampling done by the census. Thus, the entire population sampled in this study. The method used is multiple linear regression. Results reveal that for education and training variables partially significant effect on employee performance is obtained because a significant level of 0.001> 0.005. This shows the value of t> t table (2.743> 2.03), then Ho is rejected and Hi is accepted. This means that the education and training of a significant effect on employee performance. The results of the study for partial motivation variables significantly influence employee performance because significant levels obtained for 0,000> 0,005. This shows the value of t> t table (3.765> 2.03), then Ho is reject and Hi is accepted. That is the motivation significant effect on employee performance. From the test results are known regression calculation of F values obtained at 25.2544 with a significant level of 0.000 with (α) of 5% and Ftable worth 3.1504. This shows the value of F> F (25.254> 3.1504), then Ho is rejected and Hi is accepted. This means that at the same time, the variable education and training, motivation significant effect on employee performance. With the education and training, and motivation to improve employee performance.Keywords: Education and Training, Motivation, Performance